2012
DOI: 10.21273/hortsci.47.7.879
|View full text |Cite
|
Sign up to set email alerts
|

Ripening Development and Quality of Melting and Non-melting Flesh Peach Cultivars

Abstract: Some physiological and biochemical properties of melting flesh (MF) and non-melting flesh (NMF) peaches [Prunus persica (L.) Batsch] were determined during ripening for 5 days at 20 °C. Respiration rates and ethylene production of MF ‘Flordaprince’, MF ‘TropicBeauty’, NMF ‘UFSun’, and NMF ‘Gulfking’ were measured at different harvest skin ground color-based maturity stages. The MF cultivars at harvest were mostly preclimacteric or at the onset of ripening. The NMF cultivars g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
5
8
0
Order By: Relevance
“…Fruit ethylene emission appeared earlier and was greater in Oro A than in Springcrest and in Sanguinella (Fig. ), consistent with reports showing that NMF peaches generally evolve higher amounts of ethylene than MF ones (Brovelli et al , Morgutti et al , , Kao et al ).…”
Section: Discussionsupporting
confidence: 88%
“…Fruit ethylene emission appeared earlier and was greater in Oro A than in Springcrest and in Sanguinella (Fig. ), consistent with reports showing that NMF peaches generally evolve higher amounts of ethylene than MF ones (Brovelli et al , Morgutti et al , , Kao et al ).…”
Section: Discussionsupporting
confidence: 88%
“…This meant that the higher the firmness measured in nectarines, the less red peel remained, which is a sign of slowing of ripening. In fact, this parameter decreased as pulp softened during ripening as observed in other studies (Ferrer et al, 2005;Kao et al, 2012). In this sense, air-stored nectarines ripened quicker than those stored in CA and treated with 1-MCP, showing higher a* and h values.…”
Section: Effect Of Irrigation Strategy Postharvest Treatments and Tisupporting
confidence: 81%
“…Regardless of any N treatment, the NMF peaches (UFS) were firmer than the MF peaches (TB). Previous research has indicated that NMF cultivars have the capacity to hold up better in storage until the fruit reach the ready‐to‐eat stage, due to the low activity of endo ‐polygalacturonase (EndoPG) levels when the fruit are ripening . Therefore, the Florida peach industry is targeting the marketing of NMF cultivars as a tree‐ripe fruit.…”
Section: Discussionmentioning
confidence: 99%
“…In Florida, the recommended N fertilization for mature peach trees is 36–45 kg ha −1 , although many growers apply more than the recommended amount. This N rate was adapted from other peach production areas with temperate climates and different soil types, such as California, and there are few studies addressing N fertilization for peach trees in subtropical production areas .…”
Section: Introductionmentioning
confidence: 99%